PENGARUH KOMBINASI PUPUK AB MIX DAN PUPUK ORGANIK CAIR (POC) KOTORAN KAMBING TERHADAP PERTUMBUHAN DAN HASIL SAWI (Brassica juncea L.) HIDROPONIK - Purwanto, Eko; Sunaryo, Yacobus; Widata, Sri (JURNAL ILMIAH AGROUST, 2018)
This research aimed to know the influence combination of AB Mix and Organic Liquid Fertilizer (POC) made from goat manure on the growth and yield of the mustard by hydroponic. This reseach conducted by single factor experiment which arranged by Randomized Complete Block Design (RCBD) which consisted of 4 treatment levels. The first treatment was AB Mix without POC as control, the second treatment was AB Mix + POC (v/v = 3:1), the third treatment was AB Mix + POC (v/v = 1:1), the fourth treatment was AB Mix + POC (v/v = 1:3). The data analysis used analysis of variance (variance analysis) which continued by Duncan Multiple Range Test (DMRT) of 5% significance.Â  The research results showed that there was significant by difference result of the plant height, the number of leaves, the width of leaf, the fresh weight, the dry weight, and chlorophyll content. The results indicated that the treatment of AB Mix without POC as control and the treatment combinationÂ  of AB Mix + POC (v/v = 3:1) gave same results but both of the treatments gave better result that of the treatment combination of AB Mix + POC (v/v = 1:1) and the treatment combination of AB Mix + POC (v/v = 1:3). The treatment of AB Mix without POC or control showed the lower result of chlorophyll content than the combination of AB Mix + POC